Pemberdayaan Perempuan Melalui Pelatihan Life Skills Berbasis Agrobisnis di Desa Gapura Kabupaten Lombok Tengah NTB - Fajri, Siti Rabiatul; Hajiriah, Titi Laily; Fajri, Nurul; Sarnita, Fitria; Wibowo, Sarwo Edi; Armiani, Sucika; Sutajaya, I Made (Jurnal Pengabdian UNDIKMA, 2024)
This service activity aims to improve women's life skills in processing the potential of the village, namely watermelon into an agribusiness product that has a high economic selling value. The method of implementing this service uses training with target partners, namely housewives, and women of productive age in Gapura village, Central Lombok Regency, NTB. The results of this service show that this activity could improve the ability and skills of the people of Gapura Village to process watermelon into products with more selling value, namely watermelon peel and jelly candy. In addition, this activity could increase the knowledge of Gapura Village women to process agricultural products based on agribusiness. Based on the results of the evaluation, most of the partners responded that this training was very useful in improving life skills by obtaining a percentage of 55%.